2018
DOI: 10.1080/21645515.2018.1547613
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of candidate subunit vaccine against botulinum neurotoxin serotype B

Abstract: Botulinum neurotoxins (BoNTs) are potential biological weapons because of their high toxicity and mortality. Vaccination is an effective strategy to prevent botulism. The carboxyl-terminus of the heavy chain (Hc domain) is nontoxic and sufficient to generate protective immune responses against natural BoNTs in animals. To produce a vaccine suitable for human use, a recombinant non His-tagged isoform of the Hc domain of botulinum neurotoxin serotype B (BHc) was expressed in Escherichia coli and purified by sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…In the last 20 years, the immunological significance of the Hc domain of BoNTs has been the subject of intensive research, leading to important findings [14][15][16][20][21][22][23][24][25]. Our research also indicated that the Hc domain is an effective protective antigen in subunit vaccines for BoNT/A, B, E, and F [26][27][28][29]. However, the immunogenicity of other regions requires further study, such as their protective efficacy and the synergistic effects of multiple epitopes.…”
Section: Discussionmentioning
confidence: 82%
“…In the last 20 years, the immunological significance of the Hc domain of BoNTs has been the subject of intensive research, leading to important findings [14][15][16][20][21][22][23][24][25]. Our research also indicated that the Hc domain is an effective protective antigen in subunit vaccines for BoNT/A, B, E, and F [26][27][28][29]. However, the immunogenicity of other regions requires further study, such as their protective efficacy and the synergistic effects of multiple epitopes.…”
Section: Discussionmentioning
confidence: 82%
“…Reports from other studies suggested that the induction of high titer antibodies might be a better indicator of protection than other parameters used for evaluation [ 29 , 30 ]. With regard to staphylococcal superantigen toxins, specific antibodies inhibiting T-cell activation are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Purification and characterization of the recombinant Hc proteins of serotypes A, B and F have been completed, demonstrating good safety and efficacy against botulism. [23][24][25][26][27][28] In this study, we presented the production and evaluation of a recombinant non-His-tagged Hc subunit vaccine as a candidate subunit vaccine for human use against BoNT/E. The prokaryotic expression vector pTIG-Trx-EHc was successfully constructed.…”
Section: Discussionmentioning
confidence: 99%